In the reign of twilight the ironic story of a cultural exchange that typifies the 20th century - McMohan, Kevin; Primitive Features (Oley, PA : Bullfrog Films, 1994)
An investigation of the Inuit of Northern Canada and the impact of Canadian and American military installations upon their culture. Together the two countries created a high-tech outpost where the Inuit are trapped between the ancient and the post-modern. With their old economy destroyed, the Inuit turned to the creation and exporting of traditional sculpture. Includes interviews with Inuit natives, Canadian government officials and newsreel footage to highlight the social impact of military intrusion into the arctic
Copy in DVD Format
Editor, Marrin Lawrence ; director of photography, Mark Willis
Narrated by Meryn Cadell
VHS Format
English narration and Inuit with English subtitles
Keywords: Inuit -- Canada -- Social conditions; Inuit -- Canada -- Cultural assimilation; Inuit -- Canada -- Government relations; Inuit -- Canada -- History -- 20th century; Cooperative societies -- Canada -- History -- 20th century; Eskimos -- Canada -- Social conditions